#TITLE_ALTERNATIVE# - SABIQ PURWAKA (NIM 12205022); Pembimbing: Ir. Tutuka Ariadji, M.Sc., Ph.D., ZAKKI
This study is try to quantifying the various source of geology and reservoir uncertainties to study how they affect to determine ultimate recovery factor (RF) in X field. The uncertainties source of geology and reservoir are need to be studied because lack of rocks and fluids of reservoir characterization data (log, core, welltest, etc), so then later, it will change rocks and fluids of reservoir characterization data (depends on data completion), which can affect the oil recovery factor. The parameter changes which studied in this paper are : porosity, capillary pressure, formation volume factor, solution gas, water relative permeability, and oil relative permeability. From this analysis, we conclude the properties that affecting to recovery factor from highest to lowest alternately are : porosity, capillary pressure, solution gas, formation volume factor, oil relative permeability, and water relative permeability. Moreover, this study generated an equation to predict the value of recovery factor in thatÃ‚Â’s reservoir.